2014
DOI: 10.1586/14787210.2014.966082
|View full text |Cite
|
Sign up to set email alerts
|

Targeting eicosanoid pathways in the development of novel anti-influenza drugs

Abstract: The constant new emergence of life-threatening human respiratory viral pathogens presents new challenges to clinicians who are left with no available therapeutic interventions. Highly pathogenic strains of influenza A virus (IAV) share an enhanced capacity to propagate to the lower airways and paralyze alveolar macrophage antiviral capacity in order to replicate efficiently and cause pathologic inflammation. Following a century of using NSAIDs for the management of influenza symptoms, a number of studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In addition, PGE2 positively regulates enzymatic pathways critical for the suppressive function of the MDSC, including iNOS, IDO1, and IL-10. COX2 crosstalks with the IL-1/IL-1R pathway, as well as with IFN I pathway, which has been revealed in TB and flu ( 82 , 83 ). The positive cross-regulation between COX2 and IL-1 may affect M-MDSC genesis.…”
Section: Genesis Of M-mdsc In Infectious Diseasesmentioning
confidence: 95%
“…In addition, PGE2 positively regulates enzymatic pathways critical for the suppressive function of the MDSC, including iNOS, IDO1, and IL-10. COX2 crosstalks with the IL-1/IL-1R pathway, as well as with IFN I pathway, which has been revealed in TB and flu ( 82 , 83 ). The positive cross-regulation between COX2 and IL-1 may affect M-MDSC genesis.…”
Section: Genesis Of M-mdsc In Infectious Diseasesmentioning
confidence: 95%
“…ALOX15 generates 12-HETE, 15-HETE and specialized pro-resolving mediators such as lipoxin A 4 , while the cyclooxygenase pathway produces prostaglandins, including PGE 2 12 . While eicosanoid metabolites are produced in the lung at homeostasis 18 and control macrophage-mediated host defense against pathogens 13,19,20 , little is known about their contribution to lung alveolarization. In the current study, we demonstrated the critical role of the ALOX15 pathway in neutrophil-dependent AM programming in the developing lung.…”
Section: Main Textmentioning
confidence: 99%
“…In this context, the role of PGE 2 in viral infection has been documented (163). In influenza A virus infection, it was described that the augment of PGE 2 secretion inhibits type I interferon release, macrophage apoptosis, antigen presentation and T cell mediated immunity, with consequent increase in virus burden (164). Using genetic and pharmacological tools to inhibit PGE 2 production, it was shown an increase in the survival of lethally virus-infected mice, and PGE 2 inhibition was suggested as a treatment for influenza A infection (164).…”
Section: Lipid Mediators and Covid-19mentioning
confidence: 99%
“…In influenza A virus infection, it was described that the augment of PGE 2 secretion inhibits type I interferon release, macrophage apoptosis, antigen presentation and T cell mediated immunity, with consequent increase in virus burden (164). Using genetic and pharmacological tools to inhibit PGE 2 production, it was shown an increase in the survival of lethally virus-infected mice, and PGE 2 inhibition was suggested as a treatment for influenza A infection (164). More recently, in H1N1 infected obese mice, an immune suppressive role of PGE 2 was also reported, and the investigators suggested the treatment with paracetamol to restore cytokine production and to rescue lethally H1N1 infected mice from death (165).…”
Section: Lipid Mediators and Covid-19mentioning
confidence: 99%